A preliminary investigation of the effect of sample collection technique on the cell and RNA content of fine‐needle aspirates of five canine tumours. (29th November 2017) - Bowlt Blacklock, K. L.; Ireland, J.; Stewart, J.; Murphy, S.; Blackwood, L.; Starkey, M.
Abstract : Objectives: To evaluate the effect of syringe size, needle size, number of needle passes and operator experience on cell yield from tumour fine‐needle aspirates, and the quantity and quality of extractable RNA. Materials and Methods: Fine‐needle aspirates were collected from canine lymphoma, cutaneous mast cell tumour, anal gland adenocarcinoma, fibrosarcoma and oral malignant melanoma using nine different techniques. Results: There was a significant difference in cell yield between fine‐needle aspirate techniques for melanoma, lymphoma and anal gland adenocarcinoma. The application of suction yielded the largest number of cells. Cell numbers in lymphoma and fibrosarcoma aspirates collected by different veterinary surgeons were not significantly different. Use of a smaller gauge needle and suction increased the quantity of RNA isolated from fibrosarcoma and anal gland adenocarcinoma aspirates, but did not influence RNA integrity. Clinical Significance: Suction during fine‐needle aspiration increases cell numbers obtained from five common canine tumours. Suction increases the quantity of RNA isolated from anal gland adenocarcinoma and fibrosarcoma aspirates without affecting RNA quality. Junior veterinary surgeons gain comparable cell numbers to senior staff.